Membangun Kolegalitas Dosen Melalui Lesson Study Learning Community Untuk Perkuliahan Mahasiswa - Dewi, Fitri Kumala; Rini Warti; Meirisa Sahanata; Hedia Rizki; Elis Muslimah Nuraida (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
The implementation of the MBKM curriculum causes adjustments to all learning activities on campus, especially in the process of planning, implementing and evaluating lectures. The independent learning curriculum, which has been implemented since 2022, requires lecturers as teaching staff to be able to present meaningful learning. In order to achieve this goal, there needs to be collaboration between lecturers to design lecture instruments. It is expected that LSLC can enhance cooperation or collaboration among lecturers in designing more meaningful learning experiences. This aligns with the MBKM policy, which emphasizes the development of 21st-century skills and experiential-based learning. In fact, in the Tadris Mathematics study program, collaboration between lecturers in this process does not yet appear consistent and sustainable. The novelty offered by the researcher is the integration of the Lesson Study Learning Community (LSLC) approach with the Merdeka Belajar-Kampus Merdeka (MBKM) Curriculum, which has not been widely explored in higher education institutions before. This research aims to describe the process of collegiality between lecturers who teach mathematics learning media courses through the Lesson Study Learning Community. This research is a qualitative descriptive study using observation sheets, collegiality questionnaires and interview guides. The findings in this research, through LSLC activities, lecturers who teach mathematics learning media courses carry out their duties as teachers in collaboration. First, the lecturer team prepares lecture instruments together. Second, the implementation of lectures by the lecturer team formed in LSLC carries out lectures in accordance with the LSLC stages, where there are lecturers who act as model lecturers and other lecturers act as observer lecturers. Then finally, at the reflection stage, the model lecturer receives input from colleagues who are observer lecturers so that the quality of the lectures increases. Based on the results of questionnaires and interviews with the lecturer team, it shows that the lecture process is more effectively carried out in collaboration, and this indicates that collegiality is built through LSLC activities.   Penerapan kurikulum MBKM menyebabkan adanya penyesuaian-penyesuaian pada seluruh aktifitas pembelajaran di kampus terutama pada proses perencanaan, pelaksanaan, dan evaluasi perkuliahan. Kurikulum merdeka belajar menuntut dosen mampu menyajikan pembelajaran yang bermakna. Agar tercapainya tujuan tersebut perlu adanya kolaborasi antara dosen untuk merancang instrumen perkuliahan. Dimana diharapkan LSLC dapat meningkatkan kerja sama atau kolaborasi di antara dosen dalam merancang pembelajaran yang lebih bermakna. Hal ini relevan dengan kebijakan MBKM yang menekankan pengembangan keterampilan abad ke-21 dan pembelajaran berbasis pengalaman. Faktanya pada program studi Tadris Matematika, proses kolaborasi antar dosen dalam proses tersebut belum konsisten dan berkelanjutan. Kebaruan yang peneliti tawarkan adalah mengintegrasi pendekatan Lesson Study Learning Community (LSLC) dengan Kurikulum Merdeka Belajar-Kampus Merdeka (MBKM), yang belum banyak dieksplorasi pada perguruan tinggi sebelumnya. Penelitian ini bertujuan mendeskripsikan proses kolegalitas antar dosen pengampu mata kuliah media pembelajaran matematika melalui Lesson Study Learning Comunity. Penilitian ini merupakan penelitian deskriptif kualitatif dengan istrumen lembar observasi, kuesioner kolegalitas, dan pedoman wawancara. Temuan pada penelitian ini, melalui kegiatan LSLC para dosen pengampu mata kuliah media pembelajaran matematika menjalan tugas sebagai pengajar secara berkolaborasi. Pertama, tim dosen menyusun instrumen perkuliahan bersama-sama. Kedua, pelaksanaan perkuliahan tim dosen yang terbentuk dalam LSLC ini menjalankan perkuliahan sesuai dengan tahapan LSLC, dimana ada dosen yang berperan sebagai dosen model dan dosen yang lainnya bertindak sebagai dosen observer. Kemudian terakhir pada tahapan refleksi dosen model menerima masukan dari rekan-rekan yang menjadi dosen observer sehingga kualitas perkuliahan semakin meningkat. Berdasarkan hasil kuesioner dan wawancara para tim dosen ini menunjukan bahwa proses perkuliahan lebih efektif dilaksanakan secara berkolaborasi, dan ini menandakan terbangun kolegalitasnya melalui kegiatan LSLC.